1994
DOI: 10.1103/physrevlett.73.304
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of Indirect Excitons in Coupled AlAs/GaAs Quantum Wells

Abstract: The photoluminescence (PL) of excitons confined in an electric field tunable coupled AlAs/GaAs quantum well has been investigated at D350 mK and magnetic field H<14 T. In the indirect regime when electrons and holes a r e separated both in real-and in k-space, magnetic field was found t o result in (i) a strong change of both the PL intensity and decay time which i s attributed t o the anomalies in the exciton transport and (ii) an appearance of a huge broad band noise in the PL intensity which i s an evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
201
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(213 citation statements)
references
References 20 publications
9
201
0
3
Order By: Relevance
“…The onset of spontaneous coherence was evidenced by a strong enhancement of the recombination [25] and tunneling [26] rate, respectively. The results of other transport and optical experiments were also consistent with spontaneous coherence of indirect excitons [24,25,[27][28][29][30][31][32][33]. However, no direct measurement of coherence has been performed in these studies.…”
supporting
confidence: 69%
“…The onset of spontaneous coherence was evidenced by a strong enhancement of the recombination [25] and tunneling [26] rate, respectively. The results of other transport and optical experiments were also consistent with spontaneous coherence of indirect excitons [24,25,[27][28][29][30][31][32][33]. However, no direct measurement of coherence has been performed in these studies.…”
supporting
confidence: 69%
“…In these structures, the band alignments are such that electrons and holes are spatially separated in equilibrium, as the bottom of the conduction band on one side of the heterojunction lies lower than the top of the valence band on the other. Butov et al 10 have reported photoluminescence experiments in AlAs/GaAs heterojunctions, and their results suggest the appearance of a Bose condensate in at least the high magnetic field regime. Kono et al have also reported interesting spectroscopic data suggesting an infraredactive state in the InAs/Al x Ga 1−x Sb system with unusual properties, reminiscent also of those of a condensate.…”
Section: Introductionmentioning
confidence: 99%
“…The condensation of an exciton gas in semiconductors has been extensively discussed in the literature [39,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. The transition takes place when the system meets the so-called quantum degeneracy criterion nX D > 1.…”
Section: Bose-einstein Condensation and Coherent Control Of Excitomentioning
confidence: 99%
“…The finite lifetime of excitons represents an obvious drawback to achieve condensation. However, we note that typical lifetimes are long enough for the excitons to reach a quasi thermodynamic equilibrium, which can be studied using timeresolved techniques [47].…”
Section: Bose-einstein Condensation and Coherent Control Of Excitomentioning
confidence: 99%